(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
The article examines the role and place of the wolf, one of the totemic predatory animals, in the world of shamans (bakshi). The wolf is known in mythology as a protector, guardian and assistant to shamans. “Bakshi” is the name of a shaman who performs religious rites among the Kyrgyz; among the ancient Yenisei Kyrgyz, the shaman (bakshi) is mentioned in the form “kam” (in Chinese chronicles - “gyan”), Muslim sources note that kam-bakshi among the Kyrgyz were called “faginun” “.